Audit Sistem Informasi E-Kinerja Dinas Kependudukan Dan Pencatatan Sipil Kota Denpasar - Putra, Ida Bagus Agung Eka Mandala; Hartati, Rukmi Sari; Divayana, Yoga (Majalah Ilmiah Teknologi Elektro, 2020)
Abstract— Civil Servants or abbreviated as PNS represent countries that have a role in carrying out their duties to achieve the goals of the State. Contributions made by civil servants through performance affect the progress and achievement of a government agency. Staffing management at government agencies has been processed by utilizing information technology. E-Kinerja is a breakthrough by the government to measure the productivity of civil servants against responsibilities towards the main tasks and functions in achieving the objectives of government. The E-Performance information system each civil servant processes the employee performance target data input process, which is an agenda to be carried out by PNS, based on the PNS Work Behavior. The E-Performance information system of each civil servant process the employee performance targets the input data process, which is an agenda to be carried out by civil servants, based on the PNS Work Behavior. The capability of the E-Kinerja information system for staffing management needs to be evaluated. E-Performance information system audits can provide an overview, evaluation and identification of the use of information technology can provide results in terms of staffing management. COBIT 5 Framework is a collection of procedures that can meet the needs of governance and management to achieve the goals of an organization. In this research the E-Kinerja information system reaches an average value of 3.67 at level 4 (Predictble Process). Indicates that the planning of the E-Kinerja information system at the Denpasar City Population and Civil Registry Office has achieved the expected goals.